Current interdisciplinary approaches to the diagnosis of stress-related disorders: designing a study and developing the protocol for an experiment with the EyeLink 1000 Plus eye tracker - O.V. Zborovska; N.V. Rodina; O.E. Dorokhova; V.V. Kolesnichenko; V.F. Ambartsumian (Journal of Ophthalmology, 2024)
Purpose: First, to develop a combination design for a psychodiagnostic study with the formation of two experimental groups, individuals with and without stress-related disorders (SRD), and, second, to develop a design and protocol for a study that will use the EyeLink 1000 Plus eye tracker for recording eye movement parameters and assessing pupil size. Methods: The EyeLink 1000 Plus eye tracker provides highly accurate recording with a wide field of view at up to 2000 Hz. The experiment protocol includes the prosaccade task to assess the saccade latency, fixation duration, peak saccade velocity, and error rate. Screening psychodiagnostic questionnaires (the OPANA, IMZ-38 and PCL-5) and valid professional psychodiagnostic methods of Integral Instrumental Psychodynamic Diagnosis (IIPD) technology are used to form the experimental groups. Data Viewer software (SR Research) qre used for analysis of the gaze data recorded with the eye tracker. Results: We developed a combination design for a psychodiagnostic study with the formation of two experimental groups, individuals with and without SRD. In addition, we developed a detailed design for an interdisciplinary study aiming to examine eye movement parameters in the context of SRD verified by professional psychodiagnosis tools. The protocol proposed integrates the prosaccade paradigm and current eye-tracking technology, providing objective measurements and standardized conditions for the experiment. Conclusion: Conducting a study according to the design and protocol developed on the basis of an interdisciplinary approach with the use of current eye-tracking technology and psychodiagnostic methods creates the conditions for better understanding of stress-related cognitive and emotional processes, and can be useful for providing a rationale for new objective instrumental methods for the diagnosis of SRD.